2015
DOI: 10.1007/s00221-015-4472-9
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery-based skill acquisition disrupted following rTMS of the inferior parietal lobule

Abstract: Motor imagery (MI), the mental rehearsal of motor tasks, has promise as a therapy in post-stroke rehabilitation. The potential effectiveness of MI is attributed to the facilitation of plasticity in numerous brain regions akin to those recruited for physical practice. It is suggested, however, that MI relies more heavily on regions commonly affected post-stroke, including left hemisphere parietal regions involved in visuospatial processes. However, the impact of parietal damage on MI-based skill acquisition tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…() when comparing brain activation during MI before and after novices trained on a shooting task. Thus, while there is undoubtedly brain activation specific to processes that underlie MI (Hétu et al ., ; Kraeutner et al ., ; Oostra et al ., ; Ptak et al ., ), the diffuse patterns of activity generally observed during MI may not be purely indicative of a difference between MI and physical practice. Instead, we suggest that these patterns are also influenced by the degree to which the user is experienced with the skill.…”
Section: Discussionmentioning
confidence: 98%
“…() when comparing brain activation during MI before and after novices trained on a shooting task. Thus, while there is undoubtedly brain activation specific to processes that underlie MI (Hétu et al ., ; Kraeutner et al ., ; Oostra et al ., ; Ptak et al ., ), the diffuse patterns of activity generally observed during MI may not be purely indicative of a difference between MI and physical practice. Instead, we suggest that these patterns are also influenced by the degree to which the user is experienced with the skill.…”
Section: Discussionmentioning
confidence: 98%
“…Our results indicate that lesions in this region of the long associative fibers mediating the integration of visual and sensory information for motor planning and control, are associated with poor motor imagery vividness. Kraeutner et al ( 2015a ) recently demonstrated the importance of the left inferior parietal cortex (IPL) for MI performance. A preserved function of the IPL was shown to be critical for learning the cognitive aspects of a skill via MI practice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, many neuroimaging studies have established the presence of MI-induced PPC activity, as well as MI deficits following PPC damage [7, 56]. Parietal regions such as the inferior parietal lobule [57], the supramarginal gyrus [58], and the superior parietal lobule [59] have also been implicated in MI tasks. Highlighting the necessity of intact parietal structures for vivid MI, a 2016 systematic review indicated that subjects with parietal lobe damage were the most substantially impaired in their ability to perform MI [27].…”
Section: Neural Correlates Of MI and Clinical Implicationsmentioning
confidence: 99%